'It is not fair that you do not know we have problems': Perceptual distance and the consequences of male leaders' conflict avoidance behaviours. Issue 1 (February 2018) - Yang, Inju; Li, Lily Ming
Abstract: This study investigates perceptual distance in terms of managers' conflict avoidance behaviour and its consequences for subordinates. We argue that perceptual distance, or the disagreement between a manager's perception and that of his or her subordinates of his or her conflict avoidance, is a genuine phenomenon. We examine the extent to which the perceptual distance regarding managers' avoidance behaviour influences a team's justice climate as well as the role of gender. The data collected from three multinational companies in China show that the perceptual distance of a male manager's avoidance behaviour exists and that it is associated with a negative justice climate within the team. These findings provide evidence of gender's effect on leadership and highlight the benefits of female leadership.